Consumption patterns at the edge of the Roman Empire: the import of amphorae in Olisipo (Lisbon, Portugal) between the 2nd century BC and the 2nd century AD - Filipe, Victor (Rei Cretariae Romanae Fautorum Acta, 2022)
The aim of this work is to provide a synthesis of the study of the roman economy and trade in Olisipo (Lisbon, Portugal) between the Republic and the end of the 2nd century AD, based on an extended set of finds from various archaeological excavations in the ancient city of Lisbon. From the imported amphorae and its manufacturing region characterization, we will try to obtain a representative framework of the rhythms and patterns of consumption, with some brief comparisons to other cities in the province of Lusitania, during the same period. Overall, this text contributes to our understanding of the economic, social and urban conditions of the city of Olisipo, outlining the importance that it could potentially have had, at that time, in the context of the Atlantic façade and in the Roman Empire.